1992
DOI: 10.1007/bf00190992
|View full text |Cite
|
Sign up to set email alerts
|

Spinal abnormalities and the atypical form of the Mayer-Rokitansky-Küster-Hauser syndrome

Abstract: In 96 patients with congenital absence of the uterus and upper vagina, the Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome, it proved possible to distinguish between the typical and the atypical form using laparoscopy. The typical form was characterized by symmetrical nonfunctioning muscular buds (the Müllerian duct remnants) and normal fallopian tubes, and the atypical form by aplasia of one or both buds, one bud smaller than the contralateral one, with or without dysplasia of one or both fallopian tubes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 22 publications
0
14
0
2
Order By: Relevance
“…MRKH syndrome may be associated with MURCS, and the terms were first described by Duncan (1977). Renal agenesis or ectopia together with the MRKH and KF syndromes, known as the MURCS association (MU; Mullerian duct aplasia, R: renal agenesis/ ectopia; CS: cervical somite dysplasia) [2]. Only atypical form of MRKH (type-B) is associated with renal, skeletal, and ovarian abnormalities [3].…”
Section: Discussionmentioning
confidence: 99%
“…MRKH syndrome may be associated with MURCS, and the terms were first described by Duncan (1977). Renal agenesis or ectopia together with the MRKH and KF syndromes, known as the MURCS association (MU; Mullerian duct aplasia, R: renal agenesis/ ectopia; CS: cervical somite dysplasia) [2]. Only atypical form of MRKH (type-B) is associated with renal, skeletal, and ovarian abnormalities [3].…”
Section: Discussionmentioning
confidence: 99%
“…Heidenreich et al (1988) observed that the patients with the Mayer-Rokitansky-Kuster (MRK) syndrome had the typical findings of vaginal aplasia and bipartite solid uterine buds but they proposed that the term "MRKH syndrome" should no longer be used for cases with extragenital malformations. 16 Strubbe (1992) described that the typical form (type A) is characterized by symmetrical nonfunctioning muscular buds (the mullerian duct remnants) and normal fallopian tubes, and the atypical form by aplasia of one or both buds, one bud smaller than the contralateral one, with or without dysplasia of one or both fallopian tubes. Radiographs of the spine showed that congenital spinal abnormalities, especially the Klippel-Feil (KF) syndrome, were seen more in patients with the typical form.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In those cases, where the MRKH syndrome is associated with the KF syndrome, the MURCS association should be considered. 17 Strubbe et al (1994) conducted a multidisciplinary study on a total of 100 women with congenital absence of vagina and uterus, the Mayer-Rokitansky-KusterHauser (MRKH) syndrome. The purpose of this study was to discriminate typical (type A) from atypical (type B) MayerRokitanskyKuster-Hauser syndrome (congenital absence of vagina and uterus) and determine their association with renal anomalies and ovarian disease.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Elles atteignent essentiellement le rachis (20-26 %) [29,33] mais parfois aussi les extrémités et la face. Les malformations rachidiennes sont la scoliose (20 %) [30], une anomalie vertébrale (hémivertèbre, fusion vertébrale), le syndrome [34], l'agénésie ou la malformation costale, le spina bifida [33].…”
Section: Malformations Osseusesunclassified
“…Les malformations rachidiennes sont la scoliose (20 %) [30], une anomalie vertébrale (hémivertèbre, fusion vertébrale), le syndrome [34], l'agénésie ou la malformation costale, le spina bifida [33]. Au niveau des extrémités et de la face, les anomalies retrouvées sont la brachymésophalangie [35], l'ectrodactylie [36], le pouce surnuméraire [37], l'agénésie radiale [38], le syndrome de Holt-Oram (dysplasie atriodigitale) [39,40], l'asymétrie faciale [41][42][43].…”
Section: Malformations Osseusesunclassified